2011
DOI: 10.1111/j.1469-8137.2011.03802.x
|View full text |Cite
|
Sign up to set email alerts
|

BcSpl1, a cerato-platanin family protein, contributes to Botrytis cinerea virulence and elicits the hypersensitive response in the host

Abstract: Summary• Proteins belonging to the cerato-platanin family are small proteins with phytotoxic activity. A member of this family, BcSpl1, is one of the most abundant proteins in the Botrytis cinerea secretome.• Expression analysis of the bcspl1 gene revealed that the transcript is present in every condition studied, showing the highest level in planta at the late stages of infection. Expression of a second cerato-platanin gene found in the B. cinerea genome, bcspl2, was not detected in any condition.• Two bcspl1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
251
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(278 citation statements)
references
References 56 publications
8
251
3
Order By: Relevance
“…For example, during the mutualistic T. virens-plant interaction, fungal CP elicitors Sm1 (TR_82662, TA_302952, and TV_110852) and Sm2 (TR_123955, TA_88590, and TV_111830) are secreted during the first stages of root sensing and induce systemic disease resistance, conferring resistance to phytopathogens (28,29,1271,1272). In contrast, CP virulence factor BcSpl1 from Botritys cinerea has a phytotoxic function in inducing necrosis on tobacco leaves (1273). Furthermore, CPs have also been recently classified as MAMPs/PAMPs for their role during host plant colonization (1270).…”
Section: Hydrophobins and Cerato-platanin Proteinsmentioning
confidence: 99%
“…For example, during the mutualistic T. virens-plant interaction, fungal CP elicitors Sm1 (TR_82662, TA_302952, and TV_110852) and Sm2 (TR_123955, TA_88590, and TV_111830) are secreted during the first stages of root sensing and induce systemic disease resistance, conferring resistance to phytopathogens (28,29,1271,1272). In contrast, CP virulence factor BcSpl1 from Botritys cinerea has a phytotoxic function in inducing necrosis on tobacco leaves (1273). Furthermore, CPs have also been recently classified as MAMPs/PAMPs for their role during host plant colonization (1270).…”
Section: Hydrophobins and Cerato-platanin Proteinsmentioning
confidence: 99%
“…These proteins are grouped into a protein family of which CP is the first member (the "cerato-platanin family", Pfam PF07249), and like CP some of them are known for the resistance-inducing activity in plants (Djonović et al 2006;Frías et al 2011;Seidl et al 2006;Yang et al 2009;Zaparoli et al 2009). In the "ceratoplatanin family", the molecular mechanism of action on plants and above all the biological role in fungal life are little-known aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Atbak1 mutants are impaired in the perception of a plethora of fungal-, bacterial-, and oomycete-derived conserved microbial signatures (36,70,179). Yet only the identification of the novel mutant allele atbak1-5, which is specifically impaired in PTI signaling without displaying any other pleiotropic defects in development or cell-death control, revealed that AtBAK1 contributes directly significantly to disease resistance against biotrophic and hemibiotrophic pathogens (179,187).…”
mentioning
confidence: 99%